THE EFFECT OF FINANCIAL ACCOUNTING SYSTEM IMPLEMENTATION AREA ON THE QUALITY OF FINANCIAL REPORTS KUPANG CITY GOVERNMENT (Case Study on Regional Financial and Asset Management Agency) - Munawar, Munawar (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The study aims to determine the effect of the application of the local government financial accounting system on the quality of local government financial reports. The sample in this study are employees or staff in the Kupang City Regional Finance Agency. The data used in this study is questionnaire data (questionnaire) distributed to respondents or employees at the Kupang City Government Finance Agency. Questionnaires distributed and can be processed are 30 questionnaires. The analytical tool used in this study is Simple Linear Regression Analysis. The results of the Simple Regression Analysis test obtained the equation Y = 22.825 + 1.364X, the results of testing the hypothesis based on the significance value of 0.000 00 0.005 and based on the t test value the obtained value of t count with t table, namely 9.485 ÿ 2.048 which means that Ho is rejected or Ha is accepted. Based on the tests conducted, it was concluded that the application of the regional government financial accounting system affected the quality of local government financial reports by 76.3%.